On the Correlation between Alfvén Waves and Auroral Radio Emissions in the Jovian System - Yuening Chen; Zhonghua Yao; Shengyi Ye (The Astrophysical Journal)
Jupiter’s powerful aurorae reflect intense energy dissipation in the magnetosphere–ionosphere system. Recent studies reveal that solar wind compression systematically enhances auroral emission, while the mechanism is not yet fully understood. Alfvén waves were proposed to be responsible for the auroral enhancement, based on the correlation between Alfvénic wave power and ultraviolet auroral intensity revealed by the unprecedented, though limited, observations of Juno and the Hubble Space Telescope. Since auroral energy dissipation produces emissions across multiple frequency bands, we leverage a comprehensive data set of radio emissions from Juno to investigate the relation between Alfvén waves and auroral radiation power. A clear correlation between Alfvén waves and radio emissions was revealed, providing additional supporting evidence for the hypothesis that Alfvén waves contribute to auroral energy dissipation, and the correlation peaked in the region between 40 and 60 R _J , providing key insights to the Alfvénic energy source region in the magnetosphere.